(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Flora of nature territories situated along the Krynka River basin is described. 149 of 1182 species of vascular plants found here are rare ones. The map that show basic elements of a regional ecologicalal network is made. Topological efficiency of the ecological network in the Krynka River basin is characterized to be low. The reserved territory in the Krynka River basin can be increased up to 5%. All local florae studied are offered to be included in two regional landscape parks’ territories “Donetworksky Cryazh” and “Zuyivsky”.